Metabolism of bile acids, liver diseases and microbiome - Yu. V. Yevsyutina; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present the modern data on interrelation of bile acid (BA) metabolism, microbiome and liver diseases. Summary. Bile acids are important signaling molecules that regulate lipid and glucose metabolism. Enterohepatic circulation of BA plays the central role in nutrient absorption and metabolic regulation. Data of investigations demonstrate interrelation of BA, intestinal microbiome and liver diseases. In particular, the role of BA metabolism disorders in development of non-alcoholic fatty liver disease is extensively studied. Sequestrants of BA are under study as putative BA and glucose metabolism regulators then draws interest from practical point of view. Conclusion. Bile acids carry out multiple physiological functions. The link between BA metabolism, liver disease and intestinal microbiome is demonstrated by numerous investigations.